Analysis Of Family Economic Resilience Against Early Marriage Practices In Mayang Village - Qoidul Khoir; Saini; Ali Zainal Abidin (PT. Banjarese Pacific Indonesia, 2024)
This research aims to measure the economic resilience of families involved in early marriage in Mayang Village, Jember Regency. Using a mixed methods approach that combines quantitative and qualitative methods, data was collected through observation, interviews, documentation, and surveys of 50 respondents who met the criteria. Data analysis using multiple linear regression shows that family income, mother's education level, and access to social assistance programs significantly affect family economic resilience. The data processing in this research uses Descriptive Statistical Analysis to describe the economic characteristics of families, such as income, expenditure, and welfare indicators. The results of this study indicate that early marriage has a significant impact on the economic resilience of families in Mayang Village, as reflected in decreased income and increased health burdens. These findings also highlight the importance of women's economic empowerment programs and improved access to education as efforts to enhance the welfare of families involved in early marriage. Interventions targeting education, health, and changes in social norms are crucial for improving the economic resilience of families in Mayang Village.